CREATION OF AN ELECTRONIC BUSINESS DATABASE TO IMPROVE THE QUALITY OF PUBLIC SERVICES IN THE REGION - F.D. Jo'rayev,; Qobilova Muhayyo Abdurazzaqovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
The aim of the work is to develop scientific proposals and practical recommendations on the formation of a cluster information system for housing and communal services in the context of digital transformation in the context of fundamental economic reform.